Salacca acehensis (Arecaceae), A New Species from Sumatra, Indonesia - Zumaidar, Zumaidar -; Chikmawati, Tatik; Hartana, Alex; Sobir, Sobir; Mogea, Johanis Palar; Borchsenius, Finn (Phytotaxa, 2014)
A new species of Salacca sect. Salacca from Sumatra is described and illustrated. It is characterized by dwarf habit, with leaves to 2.5 m long; erect and slender staminate inflorescences to 7 cm long; and small infructescences, to 10 cm long, with up to 3 branches The most similar species, S. rupicola from Borneo, is different in having the apical leaflets composed ca. 8 united segments versus 2 in the new species, and in having larger inflorescences, the staminate to 15 cm long and the pistillate to 40 cm long.